TESTS AS A MEANS OF OBJECTIVE DIAGNOSIS OF THE KNOWLEDGE QUALITY IN THE CONTEXT OF IMPLEMENTATION OF PROBLEMATIC TEACHING FOR CLINICAL CYCLE DISCIPLINES IN A VETERINARY INSTITUTION - O E Davydova; N V Pimenov (Erudio Journal of Educational Innovation, 2018)
The principle of problem characterizes the features of an objective assessment of the quality of education in the fileld of "Veterinary". The article provides the substantiation and specificity of the methodology of test control of the level of knowledge in the disciplines of the contagious cycle, aspects of its improvement. The examples presented in the materials clearly demonstrate the adaptation of testing technologies in the system of higher veterinary education. When implementing problem training in the disciplines of the clinical cycle of veterinary education, an improved system of test-control serves as an objective indicator of the level of knowledge and ability to make operational decisions by students in the formation of their professional competencies.